2016
DOI: 10.1002/jclp.22434
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Outcomes in a Randomized Controlled Trial of a Ward‐based Intervention on Psychiatric Inpatient Wards: A Qualitative Analysis of Staff and Patient Experiences

Abstract: Objectives. Team formulation is advocated to improve quality of care in mental health care and evidence from a recent UK based trial supports its use in inpatient settings. This study aimed to identify the effects of formulation on practice from the perspectives of staff and patient participating in the trial, including barriers and enhancers to implementing the intervention.Method. We carried out semi-structured interviews with 57 staff and 20 patients. Data were analyzed using thematic analysis.Results. Main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 22 publications
4
30
2
Order By: Relevance
“…Unlike other studies of inpatient psychological intervention (Berry, Haddock, Kellett, Awenat, et al, 2016;Donaghay-Spire, McGowan, Griffiths, & Barazzone, 2016), we observed that managerial staff and psychiatrists did not attend relevant psychological training. This may suggest either a lack of support for the therapeutic approaches, time and resource restrictions, poor intervention promotion, or disparity between disciplinary models of mental illness; further research is required to establish the precise reasons.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike other studies of inpatient psychological intervention (Berry, Haddock, Kellett, Awenat, et al, 2016;Donaghay-Spire, McGowan, Griffiths, & Barazzone, 2016), we observed that managerial staff and psychiatrists did not attend relevant psychological training. This may suggest either a lack of support for the therapeutic approaches, time and resource restrictions, poor intervention promotion, or disparity between disciplinary models of mental illness; further research is required to establish the precise reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar barriers have been, and continue to be, reported in inpatient psychiatric services (Berry, Haddock, Kellett, Awenat, et al ., ; Berry, Haddock, Kellett, Roberts, et al ., ; Clarke & Wilson, ; McCann & Bowers, ). As key aims of nurse‐led group therapies are to increase access to psychological therapies and to improve therapeutic milieu, through increased psychological knowledge and skills within different staff groups, this has important implications for the reach of the intervention to both service users and staff.…”
Section: Discussionmentioning
confidence: 99%
“…These work streams will probe psychological mechanisms; barriers and facilitators to providing the CARMS trial intervention in the 'realworld'; implementation challenges and solutions; aspects of the therapy which were perceived as being both positive and negative; and the experiences of taking part in suicide research. It has been shown that qualitative work can often contextualise aspects of the design of trials which can remain hidden wherein aspects of interventions may, otherwise, be somewhat tacit [43,[121][122][123][124][125][126].…”
Section: Discussionmentioning
confidence: 99%
“…Summers ( 2006) noted that staff believed formulation sessions improved relationships and care planning, although these findings were only taken from the team perspective. Berry et al (2017) interviewed clinicians and patients involved in a ward-based intervention, which included team formulation sessions. In this study, staff and patients said formulation improved staff understanding of patients, with patients noticing more encouragement and less criticism from staff, and observing that staff seemed increasingly open.…”
Section: Involvement and Experience Of Clients And Staffmentioning
confidence: 99%